The Influence of Risk Management on Company Value Commercial Bank in Indonesia - Wulandari, Ayu; Djaja, Kerstan Nathanael; Lestari, Henny Setyo (International Journal of Accounting and Management Research, 2025)
The purpose of this study is to examine how credit risk, liquidity risk, solvency risk, bank size, and bank deposits influence the Price-Earnings Ratio (P/E ratio) of commercial banks listed on the Indonesia Stock Exchange during 2019–2023. The research is motivated by the phenomenon of fluctuating bank valuations in Indonesia’s capital market, where inconsistent findings from prior studies on risk management and firm value create a research gap. To address this, the study investigates three main independent variables—credit risk, liquidity risk, and solvency risk—and two control variables, bank size and bank deposits. Using a quantitative explanatory approach, panel data regression with fixed and random effects models was employed on 38 banks, yielding 190 observations. The results reveal that solvency risk has a significant positive effect on the P/E ratio, whereas credit risk, liquidity risk, bank size, and bank deposits show no significant impact. These findings highlight the importance of solvency management in sustaining investor confidence and firm valuation. Theoretically, this contributes to risk–value literature, while practically, it suggests that bank managers and investors should prioritize solvency stability when formulating capital structure and risk management policies.